2021
DOI: 10.1126/sciadv.abf4416
|View full text |Cite
|
Sign up to set email alerts
|

Efficient derivation of human trophoblast stem cells from primed pluripotent stem cells

Abstract: Human trophoblast stem cells (hTSCs) provide a valuable model to study placental development and function. While primary hTSCs have been derived from embryos/early placenta, and transdifferentiated hTSCs from naïve human pluripotent stem cells (hPSCs), the generation of hTSCs from primed PSCs is problematic. We report the successful generation of TSCs from primed hPSCs and show that BMP4 substantially enhances this process. TSCs derived from primed hPSCs are similar to blastocyst-derived hTSCs in terms of morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 38 publications
(61 reference statements)
5
67
0
Order By: Relevance
“…Very recently, Wei et al., ( 22 ) showed that primed PSCs convert to TSLCs under TSCM condition. They also showed that 10–12 d of BMP4 treatment could enhance the conversion process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, Wei et al., ( 22 ) showed that primed PSCs convert to TSLCs under TSCM condition. They also showed that 10–12 d of BMP4 treatment could enhance the conversion process.…”
Section: Discussionmentioning
confidence: 99%
“…1 B . Although 10 to 12 d of BMP4 treatment increased the conversion, the resultant cells showed a lower efficiency of EVT differentiation based on HLA-G expression ( 22 ). Interestingly, in our hands, longer BMP4 treatment gradually increased the expression of amnion genes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The original TSCs described by Okae et al, however, were neither patient-specific nor could they model diseases such as EOPE that clinically manifest late in pregnancy. In response to these limitations, placental researchers, including those interested in EOPE, have begun to combine TSC and iPSC technologies ( Li et al, 2019 ; Castel et al, 2020 ; Dong et al, 2020 ; Guo et al, 2021 ; Io et al, 2021 ; Mischler et al, 2021 ; Wei et al, 2021 ) and have even begun to generate TSCs directly from human fibroblasts ( Liu et al, 2020 ). Although the methods have yet to be compared, so it remains unclear which is superior for the generation of bona fide TSCs, these methods should ultimately provide necessary pregnancy disease specific in vitro TSC models.…”
Section: The Use Of Stem-cell Derived Trophoblast Models For Personal...mentioning
confidence: 99%